Perbaikan Poros Turbin dan Bearing pada PLTMH Desa Mendolo Lebakbarang Kabupaten Pekalongan - T Towijaya; Imam Prasetyo (Pusat Penelitian dan Pengabdian Masyarakat, 2026)
This community service project was conducted at the Micro-Hydro Power Plant (MHPP) in Mendolo Village, Lebakbarang Subdistrict, Pekalongan Regency. The activity focused on repairing the turbine shaft and replacing worn bearings to restore optimal operation. The turbine shaft showed significant wear, reducing efficiency and potentially causing excessive vibration. To address this, worn surfaces were welded and re-machined to standard dimensions. Bearings were replaced due to abnormal noise caused by rolling element damage, which posed a risk of further system failure. The process involved inspection, equipment preparation, repair execution, and performance testing. Results indicated improved turbine performance, reduced vibration, and elimination of abnormal noise, enhancing the reliability and service life of the MHPP. This work contributes to the sustainability of electricity supply for the local community